Comunicação ambiental e a aplicação da ISO 14063 em empresas certificadas com a ISO 14001 em Curitiba e região metropolitana - Muniz, Fábio (2008)
The following text presents an analysis of environmental communication in the Corporative environment, based on a research performed in conjunction with ISO 14001 certified companies located in the city of Curitiba and metropolitan area. This work uses the theoretical reference related to environment information, environmental communication, organizational communication and the application of ISO 14063 norm – Guidelines and examples following a qualitative approach. It also uses the reference on how to improve the environmental communication in the business environment, highlighting its necessity and importance. The analysis of this research revealed that such norm is still pretty unknown, besides its publication at the end of the year of 2006. However many of the communication tools proposed by ISO are already used by companies in the environmental communication. The research also revealed that besides the importance from the environmental communication on the behavioral changes and environmental awareness, this is still not well applied.